The Arctic polar stratospheric cloud aerosol - Aircraft measurements of reactive nitrogen, total water, and particles - Kawa, S. R.; Fahey, D. W.; Kelly, K. K.; Dye, J. E.; Baumgardner, D.; Gandrud, B. W.; Loewenstein, M.; Ferry, G. V.; Chan, K. R. (1992)
In situ aircraft measurements in the lower stratosphere are used to investigate the reactive nitrogen, NO(y), total water, and particle components of the polar stratospheric cloud (PSC) aerosol in the Arctic. The results are compared to findings from the Antarctic derived using similar measurements and interpretive techniques. The Arctic data show that particle volume well above background values is present at temperatures above the frostpoint, confirming the result from the Antarctic that the observed PSCs are not water ice particles. NO(y) measurements inside a PSC are enhanced above ambient values consistent with anisokinetic sampling of particles containing NO(y). In the Arctic data over long segments of several flights, calculations show saturation with respect to nitric acid trihydrate without significant PSC particle growth above background.